Catalysis studies of Ru3(CO)12 substituted with PPh2CH2CH2 CH2PPh2 - Fontal, Bernardo; Hernández, Ricardo; Suárez, Trino; Reyes, Marisela; Bellandi, Fernando (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF